PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA MTS POKOK BAHASAN ARITMETIKA SOSIAL - Sholahudin Al Ayubi (FKIP Universitas Islam Jember, 2016)
The purpose of the research is to know the improvement of students’ activity and student mathematic learning outcomes by using PBL model. The type of the research is classroom action research with qualiitative approach. The subjects of this research are the seventh grade students of MTs Ainul Yaqin. The subjects were observed to know activity and were given the test to know mathematic learning outcomes. The data collecting methods are documentation, observation, interview, and test. The results of the research in individual activity significantly improved from 50 % in cycle I until 76% in cycle II, then for group activity improved from 48% in cycle I until 72% in cycle II. Besides, the students learning outcomes improved from 85.29 % in cycle I with 5 from 34 students that did not pass until 88.24% in cycle II with 4 from 34 students that did not pass. The conclusions are PBL model could improve students’ activity and learning outcomes on Arithmetic Social Material. The suggestion is PBL can be an alternative model to teach mathematic, it is because this model give positive effect to students. Key Words: PBL, mathematic learning outcomes